Possibilities of utilizing power plant fly ashes - Mezencevová Andrea (Acta Montanistica Slovaca, 2003)
The burning of fossil fuels in industrial power stations plays a significant role in the production of thermal and electrical energy. Modern thermal power plants are producing large amounts of solid waste, mainly fly ashes. The disposal of power plant waste is a large environmental problem at the present time. In this paper, possibilities of utilization of power plant fly ashes in industry, especially in civil engineering, are presented. The fly ash is a heterogeneous material with various physical, chemical and mineralogical properties, depending on the mineralogical composition of burned coal and on the used combustion technology. The utilization of fly ashes is determined of their properties. The fineness, specific surface area, particle shape, density, hardness, freeze-thaw resistance, etc. are decisive. The building trade is a branch of industry, which employs fly ash in large quantities for several decades.The best utilization of fluid fly ashes is mainly in the production of cement and concrete, due to the excellent pozzolanic and cementitious properties of this waste. In the concrete processing, the fly ash is utilized as a replacement of the fine aggregate (fine filler) or a partial replacement for cement (active admixture). In addition to economic and ecological benefits, the use of fly ash in concrete improves its workability and durability, increases compressive and flexural strength, reduces segregation, bleeding, shrinkage, heat evolution and permeability and enhances sulfate resistance of concrete.The aim of current research is to search for new technologies for the fly ash utilization. The very interesting are biotechnological methods to recovery useful components of fly ashes and unconventional methods of modification of fly ash properties such as hydrothermal zeolitization and mechanochemical modification of its properties. Mechanochemistry deals with physico - chemical transformations and chemical reactions of solids induced by mechanical action. It is known, that performance of fly ash in concrete improves with its increased fineness. Intensive milling of fly ash leads to the increasing fly ash fineness and to the enhancement of its hydration activity. The cement-fly ash composites with 25 wt.% of activated fly ash as cement replacement have exhibited a higher 28-day compressive strength in comparison with a reference concrete sample without fly ash. An unfavorable effect in milling process is the agglomeration of fine particles of fly ash. By high-energy milling of fly ash with addition of surfactants, the ultrafine products can be prepared. Concrete samples containing such fly ash have achieved higher compressive strengths than the reference sample without fly ash or with addition of non-milled fly ash. The considerable physical effect of ultrafine fly ash consists in superior filling of spaces between coarser cement particles and in the favorable influence of hardness of the mixtures at setting.The current research activities in mechanochemistry are oriented to the mechanical activation of poly-component systems. The knowledge in this field indicate that by high-energy milling of fly ash as a poly-component system and following heating of prepared metastable precursors, the cement minerals could be prepared.